DISCERN-Genetics: quality criteria for information on genetic testing. - Shepperd, S; Farndon, P; Grainge, V; Oliver, S; Parker, M; Perera, R; Bedford, H; Elliman, D; Kent, A; Rose, P (2006)
Information currently available to the public is inadequate to support those deciding to consent to a genetic test. As genetic knowledge continues to evolve, more people will be forced to consider the complex issues raised by genetic testing. We developed and tested criteria to guide the production and appraisal of information resources produced for the public on genetic testing. Lay people with and without experience of a genetic condition, and providers and producers of health information appraised and listed the criteria they used to rate the quality of a sample of information on cystic fibrosis, Down's syndrome, familial breast cancer, familial colon cancer, haemochromatosis, Huntington's disease, sickle cell disease, and thalassaemia. These genetic conditions represent different populations, disease pathways, and treatment decisions. The information medium could be written, electronic, CD, audio or video. The quality criteria were tested iteratively (using the weighted kappa statistic) for the level of agreement between users applying successive drafts of the criteria to different samples of information. The final set of criteria consisted of 19 questions plus an overall quality rating. Chance corrected agreement (weighted kappa) among the appraisers for the overall quality rating was 0.61 (0.60-0.62). The criteria cover the scope of the information resources, information on the condition, the test procedure and results, decision making, and the reliability of the information. The DISCERN-Genetics criteria will guide the production and appraisal of information produced for the public, and will facilitate the involvement of the public in decisions around genetic screening and testing.